The effect of social deprivation on the incidence rate of carpal and cubital tunnel syndrome surgery. (March 2021) - Johnson, Nick A.; Darwin, Oliver; Chasiouras, Dimitrious; Selby, Anna; Bainbridge, Chris
We sought to establish whether carpal and cubital tunnel syndrome requiring surgery is associated with deprivation in England. Data from 10, 496 adult patients who were treated in our hand unit over a 20-year period were reviewed. The Index of Multiple Deprivation was used to measure deprivation from the patients' postcode. The mean age at surgery in the most deprived three quintiles was significantly lower than in the least deprived two quintiles for carpal tunnel release (55 vs 59 years, respectively) and cubital tunnel release (52 vs 57 years, respectively). The incidence rate was significantly lower for the three least deprived quintiles when compared with the most deprived quintile for both conditions. The incidence rate ratio of the least deprived quintile compared with the most deprived quintile for carpal tunnel release was 0.70 for men and 0.76 for women. The incidence rate ratio of the least deprived quintile compared with the most deprived quintile for cubital tunnel release was 0.79 for men and 0.49 for women. Carpal tunnel and cubital tunnel syndrome requiring surgery is more common in deprived patients and occurs at an earlier age. Level of evidence: IV